2019
DOI: 10.1016/j.ejvs.2019.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of the Iliac Branch Device E-liac in Patients with Common Iliac Artery Aneurysms: 12 Month Results

Abstract: WHAT THIS PAPER ADDS New dedicated iliac branch devices (IBDs) help to minimise ischaemic complications by preserving internal iliac artery (IIA) flow. There are currently three dedicated IBDs available on the market, including the E-liac Stent Graft System. The present study evaluates the safety and efficacy of this stent graft and is the first and largest prospective trial on this iliac side branch device. The favourable results demonstrate its promising performance and safe application. Objectives: At 12 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In both cases, the kinking of the EIA was identified as the reason for the thrombosis, which was fixed with the relining of the iliac limb (with PTA or bare-metal stent implantation). Brunkwall et al reported one-year results of 48 E-iliac devices and also found edge stenosis and thrombosis in two EIAs, which needed re-intervention [19]. Thus, the extern iliac artery limb of the E-iliac needs to be carefully evaluated in the completion angiography for kinking and stenosis, particularly in tortuous anatomies, as it appears to be the major complication site of this system.…”
Section: Results Of the E-iliac Ibd Studiesmentioning
confidence: 99%
“…In both cases, the kinking of the EIA was identified as the reason for the thrombosis, which was fixed with the relining of the iliac limb (with PTA or bare-metal stent implantation). Brunkwall et al reported one-year results of 48 E-iliac devices and also found edge stenosis and thrombosis in two EIAs, which needed re-intervention [19]. Thus, the extern iliac artery limb of the E-iliac needs to be carefully evaluated in the completion angiography for kinking and stenosis, particularly in tortuous anatomies, as it appears to be the major complication site of this system.…”
Section: Results Of the E-iliac Ibd Studiesmentioning
confidence: 99%
“…The PLIANT study documented the performance of the Jotec E-Iliac endograft in 45 patients; clinical success at 12 months was 90%. 13 In the pELVIS registry of over 900 IBD implants, 9 IBDs provided satisfying estimated rates of 8-year freedom from IBD and IIA occlusion (87% and 95.1%, respectively) and freedom from reintervention (85.7%) due to occlusion and/ or type I endoleak.…”
Section: Discussionmentioning
confidence: 99%
“…In the first prospective multicenter study of 52 patients with CIAAs treated with IBDs combined with different aortic components, Haulon et al [ 23 ] reported CIA shrinkage in 81% of patients at the 1-year follow-up and iliac branch occlusion in 11% of cases within the first month. Several research investigations have demonstrated outstanding early and midterm safety and efficacy of IBDs in treating aorto-iliac aneurysms or isolated CIAAs, as well as low rates of complications and mortality [ 7 , 24 ]. These results support the use of IBDs as the primary treatment option for patients with intra-abdominal aneurysms and a suitable vascular anatomy [ 15 , 25 ].…”
Section: Discussionmentioning
confidence: 99%